Identification of an Exon 4-Deletion Variant of Epidermal Growth Factor Receptor with Increased Metastasis-Promoting Capacity - Hai Wang (Neoplasia: An International Journal for Oncology Research, 2011)
Several types of epidermal growth factor receptor (EGFR) gene alternations have been observed in human tumors. Here we present a novel EGFR variant with aberrant splicing of exon 4 (named as de4 EGFR). Variant-specific polymerase chain reaction showed that de4 EGFR was expressed in some glioma (4/40), prostate cancer (3/11), and ovarian cancer (3/9) tissues but not in tissues adjacent to tumors or normal tissues. de4 EGFR displayed an enhanced transformation and a higher metastasis-promoting capacity in comparison to wild-type EGFR. With minimal EGF-binding activity, de4 EGFR underwent ligand-independent autophosphorylation and self-dimerization. Moreover, in serum-starved condition, de4 EGFR expression in U87 MG cells significantly upregulated the extracellular signal-regulated kinase and AKT phosphorylation and expression of JUN and Src. Importantly, E-cadherin expression was barely detectable in the U87 MG cells expressing de4 EGFR and restored expression of E-cadherin in these cells inhibited their metastatic behaviors. Taken together, we identified a novel EGFR variant with increased metastasis-promoting activity that may become a promising new target for cancer therapy.